Ethiopia's agrifood system: Past trends, present challenges, and future scenarios - Dorosh, Paul A.; Minten, Bart (International Food Policy Research Institute, 2020)
Ethiopia has experienced impressive agricultural growth and poverty reduction, stemming in part from substantial public investments in agriculture. Yet, the agriculture sector now faces increasing land and water constraints along with other challenges to growth. Ethiopia’s Agrifood System: Past Trends, Present Challenges, and Future Scenarios presents a forward-looking analysis of Ethiopia’s agrifood system in the context of a rapidly changing economy. Growth in the agriculture sector remains essential to continued poverty reduction in Ethiopia and will depend on sustained investment in the agrifood system, especially private sector investment. Many of the policies for a successful agricultural and rural development strategy for Ethiopia are relevant for other African countries, as well. Ethiopia’s Agrifood System should be a valuable resource for policymakers, development specialists, and others concerned with economic development in Africa south of the Sahara.